Optimal Warranty Policy Considering Two-dimensional Imperfect Preventive Maintenance for Repairable Product - Xin Yue Li; Yun Xian Jia (Institute of Advanced Engineering and Science, 2015)
For some kinds of products, such as car, aircraft, government acquisition, the consumers have strict requirements to the reliability of these products. Then the manufacturer is inclined to provide the two-dimensional preventive maintenance policy to take the usage degree of the product into account. As a result, two-dimensional preventive maintenance policy in the warranty period has recently obtained increasing attention from manufacturers and consumers. In this paper, we focused on the optimization of based warranty cost and proposed a new expected cost model of the two-dimensional imperfect preventive maintenance policy from the perspective of the manufacture. The optimal two-dimensional preventive maintenance was obtained by minimizing based warranty cost. And asymmetric copula function was applied to modeling the failure function of the product. At last, numerical examples are given to illustrate the proposed models, of which the results prove the model effective and validate. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7043